Feeding Cattle. Feeding cattle at critical times during the dry season in the Las Segovias area of Nicaragua - Rodríguez Portillo, Saúl Armando; Rodríguez Mejía, Giovanni Rodolfo; Marín Marín, Yamil Ernesto; Rodríguez Chávez, Delio (Catholic Relief Services, 2015)
This publication the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprises Management, Health, and the Environment (PROGRESA). This document systematizes PROGRESA's experiences in the use of innovative forage conservation technologies to feed cattle in dry areas during the dry season.